Cover Image. (16th July 2021) - Bayerl, Paul; Folchert, Nils; Bayer, Johannes; Dzinnik, Marvin; Hollemann, Christina; Brendel, Rolf; Peibst, Robby; Haug, Rolf J.
Abstract : The cover image is based on the Research Article Contacting a single nanometer‐sized pinhole in the interfacial oxide of a poly‐silicon on oxide (POLO) solar cell junction by Paul Bayerl et al., https://doi.org/10.1002/pip.3417 .